'I feel like a snake changing its skins': a plurilingual project. (27th December 2021) - Celaya, M Luz; López-Flores, Silvia
Abstract: In line with the directions of the Council of Europe on the teaching of foreign languages to young learners and in view of recent waves of immigration in Europe, special emphasis is nowadays being placed on plurilingual and pluricultural practices in the school system. This paper describes the change towards embracing plurilingualism in a primary school in Barcelona (Spain) to try to cater for the students' home languages and for cultural diversity in the EFL classroom. Results show that both the cohesion between the school and the families, and respect for and understanding of diversity were favoured, and that the level of competence in English at the end of primary education in this school was higher than the average of schools in the same context.